2009
DOI: 10.1002/ajim.20744
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and atypical jobs in France, from the 2003 Decennial health survey

Abstract: The associations between atypical jobs and depressive symptoms differ for job status according to sex and do not seem to be associated with the worst psychosocial working conditions. The interpretation of these results is nonetheless limited in part by the cross-sectional nature of the survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
3
25
0
3
Order By: Relevance
“…One reason for this mixed evidence may be that non-permanent employees are not a homogeneous group and several factors, including sociodemographics, might modify the association between employment status and mental health (7)(8)(9)(10)(11)(12)(13)(14). A previous study from the same dataset used in this study found consistent socioeconomic inequalities in the onset, duration, and recurrence of work disability (15).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…One reason for this mixed evidence may be that non-permanent employees are not a homogeneous group and several factors, including sociodemographics, might modify the association between employment status and mental health (7)(8)(9)(10)(11)(12)(13)(14). A previous study from the same dataset used in this study found consistent socioeconomic inequalities in the onset, duration, and recurrence of work disability (15).…”
mentioning
confidence: 84%
“…This is important because earlier evidence suggests that the effects of temporary employment on health might be more adverse among women (13,14,19) and those with a lower level of education (11).…”
Section: Covariates and Effect Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Taki wynik uzyskali Santin i wsp. [27]. W ich badaniu, przeprowadzonym wśród pracowników zatrudnionych na czas określony, znaczą-cy związek z depresją stwierdzono jedynie w grupie kobiet.…”
Section: Rodzaj Umowy O Pracę a Zdrowie Pracownikówunclassified
“…In France, among men and women, constrained part-time work is associated with a higher depression. From the 2003 Decennial Health Survey, Santin et al (2009) show that having a fixed-term contract is correlated with depression, but only for women. Workers on temporary contracts may suffer more psychological costs and stress due to exposure to job insecurity (Ferrie, 2001;Ferrie et al, 2005;Chenga Yawen et al, 2005;Green, 2011;Caroli and Godard, 2013).…”
mentioning
confidence: 99%